(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2024)
Why IPS (Indoor Positioning Systems)? This issue is one of the most challenging things to solve in wireless localization due to the lack of a Global Positioning System (GPS) and the existence of distinctive radio propagation characteristics. Although there are different localization options available, the accuracy of localization cannot satisfy customers’ requirements. Positioning algorithms could be grouped into two groups, including range-based and range-free techniques. Before actually putting a localization technique into practice, the accuracy of those techniques is of the utmost importance. Range-based methods can often attain great accuracy with the help of specialized hardware, and this accuracy can be dependent on either the distances between nodes or the angles between them. In this paper, a comparison of different strategies utilized for positioning is presented, as well as an analysis of the pros and cons associated with supporting technologies for each strategy. A literature survey of the recent IPS technologies range-based with focuses on Ultra-Wide Band (UWB) and Light Fidelity (Li-Fi) is presented with significant recommendations. This literature considered the accuracy, complexity, scalability, cost, latency, deployment, and usability, as well as strengths, shortcomings, approaches, and issues determined by each work. This paper highlights the most recent research gaps and reviews the most promising findings, with recommendations to the reader and researcher, in UWB and Li-Fi indoor positioning systems over the last five years based on range-based techniques. In addition, this paper serves as a guide that discusses all of the measures that may be utilized in the process of evaluating localization technologies, and it could be considered a roadmap for existing and new researchers to identify and characterize suitable technologies for creating innovative systems and apps via stand-alone range-based positioning.